Long‐term safety of linagliptin monotherapy in Japanese patients with type 2 diabetes. Issue 4 (7th December 2012) - Araki, E.; Kawamori, R.; Inagaki, N.; Watada, H.; Hayashi, N.; Horie, Y.; Sarashina, A.; Thiemann, S.; von Eynatten, M.; Dugi, K.; Woerle, H.‐J.
Abstract : Aims: In a phase III study conducted among Japanese patients with type 2 diabetes mellitus (T2DM), linagliptin 5 and 10 mg showed clinically meaningful improvements in glycaemic parameters after 12 and 26 weeks compared with placebo and voglibose, respectively. This extension study assessed long‐term tolerability of linagliptin over 52 weeks. Methods: Japanese patients with T2DM who completed either phase of a 12‐week/26‐week study comparing linagliptin monotherapy with placebo or voglibose were eligible to enrol. In the extension study, the comparator groups switched to linagliptin 5 or 10 mg, while the linagliptin groups maintained dosage. Results: In all, 540 patients received at least one dose of linagliptin 5 or 10 mg and 494 completed the extension. Long‐term treatment with linagliptin was well tolerated; adverse events (AEs) of special interest and serious AEs occurred in small percentages of patients. Drug‐related AEs occurred in 10.2 and 10.6% of patients in the linagliptin 5‐ and 10‐mg groups, respectively, and discontinuations due to drug‐related AEs occurred in 1.1 and 0.7%, respectively. Only one (0.4%) patient in each dose group experienced investigator‐defined hypoglycaemia during the treatment period (both events were non‐severe). Body weight was not clinically altered in either group. The glycated haemoglobin A1c profiles over time were similar with linagliptin 5 and 10 mg. Conclusions: These findings provide evidence for the safety and tolerability of oral linagliptin at either 5 or 10 mg for up to 52 weeks for the treatment of Japanese patients with T2DM, without clinically relevant increase in the risk of hypoglycaemia or weight gain.